Effect of l-carnıtıne used ın regular exercıse ın elderly obesıs rats - Aynur Başalp; İbrahim Kubilay Türkay (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to investigate the effect of L-Caritine supplemented elderly rats on weight loss during 12 weeks. This experimental study was carried out on experimental animals in a scientific laboratory environment, under defined conditions and according to the method of application. Therefore, the model of the research is an experimental research model. In this study, 8 obese aged rats were used for 20 months. Approximately 70 years of human life is equivalent. The rats were given special cholesterol food for obesity. In the study, L-Carnitine was administered to the experimental group 3 times a week just before the exercise, with the daily dose of the sublingual fluid administered to the rats in a suitable dose (1 gr./kg). Before the exercise + L-Carnitine application, weight measurements of the rats were recorded at the beginning of the study (day 1), in the middle of the study (day 45) and finally at the end of the study (day 90). The “IBM SPSS Statistics 22 analiz package program was used to evaluate the statistical analysis of the study. Normal distribution assumptions were evaluated with Kolmogorov-Smirnov and Shapiro-Wilk tests. In the rare cases where the two tests are contradictory, the Kolmogorov-Smirnov test result, which is more preferred in small data sets, was used. Type 1 error margin for normality tests is taken as 0.05. At the end of the study, it was determined that the weight of the old obese rats who used L-Carnitine together with the regular exercise for 12 weeks, both on the 45th and 90th days, was found.